Changes in the Polish Administrative Judiciary (Selected Issues) - Dębski, Maciej (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
The study presents an overview of the history of administrative judiciary in Poland and the current directions of its changes. In particular, the evolution of the scope of cognition of administrative courts, the progressing computerization process and the discussion on the model of adjudication were indicated. At the same time, the challenges related to the presented directions of changes were noticed and potential solutions were indicated that would help to face them. In conclusion, it was assumed that the development of administrative judiciary ensures respect for the individual’s subjective rights in relations with administrative bodies.